Mobile-phone text messaging to promote ideal cardiovascular health in women. Issue 1 (9th February 2023) - Acevedo, Monica; Varleta, Paola; Casas-Cordero, Carolina; Berríos, Amalia; Navarrete, Carlos; Valentino, Giovanna; Lopez, Rosario; Smith, Sidney C
Abstract : Objective: Ideal cardiovascular health (CVH) was developed to promote CVH as a key component of primordial prevention. Mobile short message service (SMS) is useful for improving health behaviours. We aim to test the effectiveness of SMS intervention in women to improve CVH. Methods: In a single-blinded, randomised, controlled study, 620 women, aged 35–70 years, without cardiovascular disease, were enrolled in SMS intervention versus no SMS. CVH metrics by self-report, and biochemical laboratory, anthropometric and blood pressure measurements were collected during home visits at baseline and 9 months. Women were categorised as having poor (0–2), intermediate (3–4) or ideal (5–7) CVH according to the number of ideal CVH metrics. Participants were randomised 1:1 to SMS intervention versus control. SMS was sent every 5–6 days for 9 months. The primary outcome was the difference in the proportion of women with ideal CVH between SMS and control groups at 9 months. Rates of intermediate CVH, poor CVH and each of the seven ideal CV health metrics at 9 months were key secondary endpoints. Results: At 9 months, there was no significant difference between groups for the primary outcome (16.3% at baseline and 13.3% at 9 months, and 10.1% and 11.1%, in SMS and control groups, respectively, adjusted RR 1.0; 95% CI 0.6 to 1.6). Similarly, there were no significant differences between groups for the key secondary endpoints. SMS had an acceptance rate of 94.9%. Conclusions: Behavioural SMS intervention did not improve rates of ideal CVH in women, despite being feasible and well received. Trial registration number: 6377.